The cutting-off way : Indigenous warfare in eastern North America, 1500-1800 - Lee, Wayne E., 1965- (The University of North Carolina Press, 2023)
"The cutting-off way of war recasts Indigenous warfare via the lived realities of Indigenous people. Lacking deep reserves, subject to coercive military recruitment, and wary of heavy casualties that tended to amass from siege warfare, Indigenous warriors generally sought to surprise their targets, and the size of the target varied with the size of the attacking force. Lee demonstrates how it worked, detailing Indigenous warfare from precontact through the American Revolution"--